Prevalence and Influencing Factors of Anxiety and Depression Symptoms in the First-Line Medical Staff Fighting Against COVID-19 in Gansu - Zhu, Juhong; Sun, Lin; Zhang, Lan; Wang, Huan; Fan, Ajiao; Yang, Bin; Li, Wei; Xiao, Shifu (Frontiers in Psychiatry, 2020)
Abstract BACKGROUND: The outbreak of novel coronavirus pneumonia (COVID-19) has brought enormous physical and psychological pressure on Chinese medical staff. It is extremely important to understand the prevalence and influencing factors of anxiety and depression symptoms in first-line anti epidemic medical staff and their coping styles for these negative emotions. METHODS: A cross-sectional survey was conducted in Gansu (China), with a questionnaire packet which consisted of the self-rating anxiety scale (SAS), self-rating depression scale (SDS) and the simplified coping style questionnaire (SCSQ). A total of 79 doctors and 86 nurses participated in the survey. Correlation analysis was performed to explore the relationship between SAS, SDS and SCSQ score. A linear regression model was placed at determine the influencing factors for anxiety or depression symptoms. RESULTS: The prevalence rate of anxiety and depression symptoms among doctors was 11.4% and 45.6%, respectively. And history of depression or anxiety (T=-2.644, p= 0.010, 95%CI: -10.514~-1.481) was a risk factor for anxiety symptoms in doctors, while male (T=2.970, p=0.004, 95%CI: 2.667~13.521) was a protective factor for depression. The prevalence rate of anxiety and depression symptoms among nurses was 27.9% and 43.0%, respectively. And history of depression or anxiety was a common risk factor for anxiety symptoms (T=-3.635, p=0.000, 95%CI: -16.360~-4.789) and depression symptoms (T=-2.835, p=0.005, 95%CI:-18.238~-3.254) in nurses. The results of partial correlation analysis (controlled for gender and history of depression or anxiety) indicated that the total score of positive coping was negatively correlated with the total score of anxiety (r=-0.182, p=0.002) and depression (r=-0.253, p=0.001). CONCLUSIONS: The first-line anti epidemic medical staff has high anxiety and depression symptoms, and adopting positive coping style will help to improve their negative emotions.